Helloooo! Marie Here!!
The answer is:
B. (x-6)(x + 2)
Step-by-step explanation:
- If any individual factor on the left side of thee equation is the same as 0 , the entire thing will be the same as x- 6 = 0, x + 6 = 0
- Set the first factor the same as 0 and solve it x = 6
- Set the next factor equal to 0 and solve it x = -2
- The final thing to do is to add all of the answers you got that will make (x - 6) (x + 2) = 0....... x = 6, - 2
- And thats how you get B. (x-6)(x + 2)
Hope This Helps! Have A GREATTT Day!